Políticas públicas e juventudes : a participação juvenil para o acesso ao fundo público no Brasil - Reis, Denise Maria (2016)
In this study, we discuss the ways are taken by organizations and youth movements, among those who have been recognized institutionally, in construction of the access to public funds for the sake of youth policies realization, in a historical context of programs and actions targeted for youth. It also discusses the changes of political actors of the National Youth Council (Conjuve) around the public fund, its contradictions and tensions. The starting point was the Conjuve, with the focus on the participation of three elected collective for the composition of the management 2012-2013 – Studies Center and Youth Memory (CEMJ), National Black Youth Forum (FONAJUNE), Brazilian Union of Secondary Students (UBES) – and two collective of the management 2014-2015 – National Organization of Blind Brazil (ONCB) and Marist Union of Brazil (UMBRASIL) –, besides having been heard other political actors of the Council. Data were collected through interviews, participation and observation of activities and events, examination of documents, and treated by content analysis in a comprehensive and critical perspective. The results indicated that the defense of access to public funds is in the discursive level of political actors and that there are inaccuracies about the Conjuve functions and even the absence of procedural powers to carry out effective proposals, including budgetary matters. There is coexistence, in the reality of Brazilian youth, of demands for redistribution of income and demands for recognition of their identity and existence, as well as the strong presence of political parties and the student movement in the leadership of political actions and debates, although the speech is directed to the participation of several youths. The accomplishment of institutional political reform it’s important and the revitalization of democratic political culture is required as a possibility to make the existence of the speech for access to public funds and youth policies in Brazil.